1973
DOI: 10.1111/j.1432-1033.1973.tb03113.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Aspects of Heterologous Blood‐Group‐P1 Substance

Abstract: Blood-group-P, substance from sheep hydatid-cyst fluid was purified by a combination of gel filtration through Sepharose 6B and preparative polyacrylamide-gel electrophoresis. The resultant glycoprotein contained D-galactose ; D-glucose ; N-acetyl-D-ghcosamhe and N-acetyl-D-galactosamine in molar ratios 5.2 : 1 : 2 : 2; unidentified carbohydrate was also present. The amino-acid composition resembled that of vertebrate A, B, H and Lewis active glycoproteins.Prolonged incubation of P, substance with coffee bean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Free sialic acid, either 35 ,ag membrane protein was loaded on each track and the blots were treated as follows: track 1 was stained with aurodye for total protein; track 2 was treated with periodate followed by peroxidase-hydrazide reagent to reveal glycophorins; tracks 3-5 were labelled with 125I1 sialoadhesin either alone (track 3), following treatment of the blot with neuraminidase (track 4) or in the presence of 20 14g/ml F(ab')2 of the inhibitory antibody 3D6 (track 5). Sialoglycoproteins (SGP) are labelled according to the nomenclature proposed by Anstee (Anstee et al, 1979).…”
Section: Inhibition Of Sialoadhesin-mediated Haemagglutinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Free sialic acid, either 35 ,ag membrane protein was loaded on each track and the blots were treated as follows: track 1 was stained with aurodye for total protein; track 2 was treated with periodate followed by peroxidase-hydrazide reagent to reveal glycophorins; tracks 3-5 were labelled with 125I1 sialoadhesin either alone (track 3), following treatment of the blot with neuraminidase (track 4) or in the presence of 20 14g/ml F(ab')2 of the inhibitory antibody 3D6 (track 5). Sialoglycoproteins (SGP) are labelled according to the nomenclature proposed by Anstee (Anstee et al, 1979).…”
Section: Inhibition Of Sialoadhesin-mediated Haemagglutinationmentioning
confidence: 99%
“…Sialoadhesin bound to several membrane proteins in a specific and sialic acid-dependent manner (Figure 4, lanes 3-5). Using a peroxidase-hydrazide reagent to detect sialoglycoproteins (Gershoni et al, 1985), all of the recognized bands corresponded to glycophorins, either monomers of glycophorin A and C (a and 1 in Figure 4), homodimers of glycophorins A and B or heterodimers of glycophorins A and B (a2, 62 or ab in Figure 4 respectively) (Anstee et al, 1979). However, bands r (component E) and 6 (monomeric glycophorin B) were apparently not recognized by sialoadhesin under the conditions used.…”
mentioning
confidence: 99%
“…Achatina granulata (freeze-dried albumin glands) was from Dr. S. Khalap, Metropolitan Police Forensic Science Laboratory, London SE1 7JH, U.K.; 100mg was dissolved in 1 ml of phosphate-buffered saline. The preparation of crude extracts of other lectins used has been described (Anstee & Pardoe, 1973). The lectins from Maclura aurantiaca, Helix pomatia and Triticum vulgaris (wheat-germ agglutinin) were used after purification by absorption and elution from formaldehyde-treated human erythrocytes.…”
Section: Lectinsmentioning
confidence: 99%
“…V erythrocytes SDS/polyacrylamide-gel electrophoresis. Our previous studies on cells heterozygous for the Mi.V condition suggested that these cells contained decreased amounts of component a and increased periodate staining in the region of component f, (Anstee & Tanner, 1978). Further investigation of membranes from these cells has shown that, in addition to the increased staining in the region of component ,B (apparent mol.wt.…”
Section: Resultsmentioning
confidence: 94%
“…The Mk condition is associated with the loss of MN and Ss antigens and has been shown to be accompanied by the absence of component a (Dahr et al, 1977;Anstee & Tanner, 1978;Furthmayr, 1978). On the basis of decreased periodate/Schiff staining of component in Mk heterozygotes, Dahr et al (1977) concluded that the Mk condition was also associated with the absence of this component.…”
Section: Membranes From Mkimiiii Erythrocytes and The Nature Of The mentioning
confidence: 99%